Carrier rocket-inspired hydrogel microspheres targeting subchondral bone osteoclast activity alleviate osteoarthritic pain and cartilage degeneration - Zhenglin Zhu; Yujia Luo; Pengcheng Xiao; Yi Xie; Jun Zhang; Ke Huang; Xiangdong Wu; Ke Lu; Yuting Zhang; Jianye Tan; Hong Chen; Wei Huang; et al. (Journal of Nanobiotechnology)
Abstract Background Osteoarthritis (OA) represents a major global health challenge, characterized by progressive cartilage degeneration and subchondral bone remodeling, which culminate in debilitating pain and functional impairment. While recent studies have underscored the pivotal role of activated osteoclasts in the pathogenesis of OA and its associated pain, the therapeutic potential of intra-articular drug delivery has been hindered by challenges such as rapid synovial clearance and the poor permeability of cartilage, limiting the effective inhibition of subchondral osteoclast activity. Methods Sixth generation polyamidoamine (PAMAM) dendrimers were used to delivery pamidronate disodium (PD) penetrating cartilage (PD@PM). PD@PM was loaded in aldehyde modified hyaluronic acid methacrylate (AHAMA) (PD@PM@MG), to facilitating the joint injection and conglutinating on the cartilage. Therapeutic effects of PD@PM@MG were validated by in vitro and in vivo OA models. Results PD@PM@MGs microspheres are uniformly distributed across the cartilage surface and sustained releasing of PD-loaded PAMAM. The positively charged PD-loaded PAMAM (< 10 nm) efficiently permeates the cartilage matrix, neutralizes damage-associated molecular patterns, and effectively inhibits subchondral osteoclasts activities. Mice OA model tests demonstrated that intra-articular injection of PD@PM@MGs markedly alleviated arthritic pain, mitigated cartilage degeneration, and attenuated subchondral bone remodeling. Conclusions The intra-articular injection of PD@PM@MGs significantly alleviates OA symptoms and progression, offering a novel direction for clinical OA intervention. Graphical Abstract